Demographic and Regional Mortality Trends in Adult Epilepsy-Related Mortality in the United States (1999–2020) - Syeda Fadak Zahra Hujjat (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: This study utilizes data from the CDC WONDER database to assess epilepsy-related mortality trends in U.S. adults aged 25 to 85+ from 1999 to 2020. By stratifying mortality patterns demographically and geographically, the study aims to provide actionable insights to inform health policy and guide targeted interventions to reduce epilepsy-related mortality nationwide. Objective: To evaluate epilepsy-related mortality trends among U.S. adults (1999–2020) by age, sex, race/ethnicity, and geography. Materials and Methods: Retrospective observational analysis using CDC WONDER mortality data (ICD-10 codes G40–G41). Crude death rates (CDR) and age-adjusted mortality rates (AAMR) were calculated per 100,000 adults (≥25 years) to assess national trends in epilepsy-related mortality among U.S. adults. These rates were examined across multiple age groups, with 95% confidence intervals (CIs) calculated for each estimate. Age-adjusted mortality rates (AAMRs) were computed to evaluate mortality trends independent of age distribution. Trends were stratified by demographics and geography. Joinpoint regression identified temporal inflection points. Results: Nationally, CDR nearly doubled (0.6 to 1.1/100,000), with accelerated AAMR increases post-2011 (APC +9.56%, p<0.001). Demographics: Males had persistently higher mortality (AAMR 10.5 vs. 6.0 in 2020). Black individuals bore the highest burden (AAMR 13.0/100,000 in 2020). The 25–34-year age group saw the sharpest rise (AAMR: 3.0 to >14.0). Geography: High-burden states included Michigan (AAMR 1113.26), California (746.46), and Florida (518.55). Central/Northwestern states had suppressed data due to low counts. Conclusion: Epilepsy-related mortality increased significantly, with marked disparities among young adults, males, Black populations, and specific states. The inflection point (2011) suggests evolving risk factors or care gaps. Targeted interventions addressing structural inequities and geographic resource allocation are urgently needed. Keywords: Epilepsy/mortality, Health Status Disparities, United States/epidemiology, Retrospective Studies, Population Surveillance